UNLOCKING KNOWLEDGE: KEY PEDAGOGICAL ASPECTS OF THE STUDY OF PHILOLOGY - Ganiyeva Muborak Odilovna; Ergasheva Durdonakhon Gayratkhuja kizi (QO‘QON UNIVERSITETI XABARNOMASI, 2023)
The educational foundations of philology - a field of study devoted to interpreting the linguistic complexity of historical written sources—are explored in this abstract. With a focus on interdisciplinary approaches, we investigate how language analysis, literary analysis, historical study, and cultural discovery may all be integrated as vital elements of a successful philological education. Language competency, which goes beyond fluency in one's mother tongue, is vital and calls for students to learn not only syntax and vocabulary but also the subtle changes that languages undergo over time. One of the most important aspects of philological education is helping students to traverse the socio-cultural environments in which languages flourish by helping them to comprehend historical contexts. Textual analysis is emphasized as a crucial method for gaining access to knowledge, including the understanding of ancient languages, the identification of linguistic patterns, and the interpretation of cultural. The main conditions as a result of the research modernization and introduction of innovative methods in foreign systems philology of university students was analyzed.